A prospective interventional study of postoperative pain, healing rates and incontinence rates following ligation of intersphincter fistula tract procedure - P., Arunraj; S., Viswanathan M.; R., Anbazhagan; Singh, Kulwant (International Surgery Journal, 2018)
Background: Fistula in ano is one of the oldest ailments known to us, troublesome both to the patient and also challenging to the treating surgeon. The treatment of fistula in ano has evolved so much, to reduce complications and to improve patient’s compliance. This study was conducted to compare the age old method of open fistulectomy to that of recently developed technique of ligation of intersphincter fistula tract (LIFT), in patients suffering from low fistula in ano. Methods: A totally of 80 patients, suffering from low anal fistula was divided randomly into two groups. Group A: undergoing LIFT procedure and Group B: undergoing open fistulectomy procedure .The two groups were compared in the postoperative period for wound healing, postoperative pain (by visual analog scale) and fecal incontinence (by Wexner incontinence score). Results: Group A patients who underwent LIFT at the end of 3rd postoperative week had a pain score of 0.43 when compared to group B patients (1.33) who underwent fistulectomy. Group A patients had 100% continence preservation, whereas a 17.5% of moderate incontinence was documented in Group B patients. About 97.5% of patients under Group A had complete wound healing by the 3rd postoperative week, as compared to group B patients, where100% complete wound healing was noted at 6 weeks, postoperatively. Conclusions: It was found that LIFT was a promising procedure in reducing the postoperative pain significantly, with better wound healing rates. It was effective in maintaining good sphincter function, thereby providing better faecal continence following surgery, in low anal fistula.